Siladang Women and Regional Head Election in Mandailing Natal District, Indonesia - Armansyah Matondang; Yurial Arief Lubis (Budapest International Research and Critics University, 2018)
Perempuan Siladang is an ethnic minority that dwells in Mandailing Godang (Gross Mandailing) in the designation of the Dutch colonial government. This ethnicity has a patrilineal kinship system. The area is now in Mandailing Natal District and precisely in the present Panyabungan sub-district. As a minority the Siladang people tend to be retarded. Compared to neighboring ethnic groups which have been more advanced since the colonial era. Siladang people also did not escape the dynamics of local politics in Mandailing Natal District, their most obvious involvement can be seen when regional elections took place and it was known that their level of understanding of democracy was still very low. Their motives in making choices and voting are still laden with interests in the form of direct material rewards and indirectly strengthened in return. It is known that there is freedom in determining the choice and voting for the pairs of regional head candidates by Siladang women even though there is a dynamic process with other family members in the election process.